y=12-(4(6-y))

Simple and best practice solution for y=12-(4(6-y)) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=12-(4(6-y)) equation:



y=12-(4(6-y))
We move all terms to the left:
y-(12-(4(6-y)))=0
We add all the numbers together, and all the variables
y-(12-(4(-1y+6)))=0
We calculate terms in parentheses: -(12-(4(-1y+6))), so:
12-(4(-1y+6))
determiningTheFunctionDomain -(4(-1y+6))+12
We calculate terms in parentheses: -(4(-1y+6)), so:
4(-1y+6)
We multiply parentheses
-4y+24
Back to the equation:
-(-4y+24)
We get rid of parentheses
4y-24+12
We add all the numbers together, and all the variables
4y-12
Back to the equation:
-(4y-12)
We get rid of parentheses
y-4y+12=0
We add all the numbers together, and all the variables
-3y+12=0
We move all terms containing y to the left, all other terms to the right
-3y=-12
y=-12/-3
y=+4

See similar equations:

| -(-a+12)+15=51+(-6+7a) | | 4^x=3/2+5 | | x=10-(4(6x)) | | -7-6=2x-103 | | y÷20=4 | | 1/3x-1/4=1 | | 11y=120 | | -113-3x=202-12x | | 7x+18=84 | | 2r+24=88 | | -5x-5=-4x+5 | | 6.2h=80.6 | | 1y=0+-32.04 | | 3x+10=26+5x | | x+5=8x | | -118=-x3+6 | | k-5=-8+2k | | 273=210-u | | 8+3z=7(9-4z) | | -8+7x-4x=19 | | 53=v^2+3 | | x3-x=80 | | 2(x-3)=26 | | 5x+34+8x+15=80 | | 4x-50=x-10 | | -8d=-3 | | 0=2.67x+-32.04 | | z+36/8=10 | | x+7=x/2+9 | | 8x2=-11x-7 | | 7(m+4)=98 | | 10=7x-3x+6 |

Equations solver categories